Analisis Optimalisasi Sistem Administrasi Guna Meningkatkan Efisiensi Layanan di Bengkel Mobil Yuda Palembang - Islamy, Diah Putri; Sakir, Icuk Muhammad; Sutinah, Sutinah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
The car repair shop business is an attractive business in terms of the market and market demand and will continue to grow as long as there is an increase in the number of passenger car sales and the population. The development of the automotive industry has not been balanced between the growth in the number of workshops supporting equipment buying and selling services and also service workshops. The use of technology can support and increase the success of business activities, so many companies are competing to apply technology to compete with other companies. Given the rapid advancement of technology, companies must stay up to date on current technological advances and strive to surpass their competitors. This research uses a qualitative approach, data or information is collected through interviews with informants, the data is analyzed through three stages, namely. Reduction, presentation of data and conclusions. The results of this research are that the services provided by Yuda's workshop are generally good, including honesty, politeness and friendliness, fairness, speed and accuracy in work, good quality of goods, standard (competitive) prices for the services provided. However, there are still some things that are still not there, including cleanliness that is still lacking, facilities that are still incomplete and the availability of goods that is still incomplete and administrative technology that is unclear and does not exist. So there is no customer data.